Parametric geometry modeling of flying wing UAV configuration integrated with intake and exhaust - FANG Xinrui; YU Xiongqing (Hangkong gongcheng jinzhan, 2024)
Flying wing is a preferred configuration for unmanned combat air vehicle（UCAV），in which its airframe is highly integrated with intake and exhaust of propulsion system. To implement rapid geometric model of flying wing UCAV concept，a parametric geometry modeling method for flying wing UCAV configuration integrated with the intake and exhaust is proposed in this paper. Firstly，parametric models for configuration of the flying wing airframe and the intake and exhaust are established using class function/shape function. Then，the related geometry parameters between the flying wing airframe and the intake and exhaust are identified，and the correlative control rules are set to match airframe-propulsion interactions. 3D geometric models of the flying wing UCAV configuration are automatically generated by use of the parametric geometry model and CATIA API. Application examples indicate that flying wing UCAV configurations can automatically adjust its shape to match the different intake and exhaust concepts by use of the proposed method. The method can effectively improve efficiency for flying wing UCAV conceptual design.